2014
DOI: 10.1007/s12070-014-0779-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Early Onset of Hearing Loss in Young Adults With Diabetes Mellitus Type 2 Using High Frequency Audiometry

Abstract: Diabetes mellitus (DM) is a metabolic disorder caused by hyperglycemia which leads to dysfunction of various organs. Hearing acuity is equally hindered by this disorder. Among individuals with DM audiological characteristics of DM type 1 are of great concern in the literature. This study aims at establishing high frequency audiometry (HFA) as a useful tool in identifying early onset of hearing loss in individuals with DM type 2. 20 non-diabetic participants and 20 individuals with DM type 2 in the age range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“… 37 , 38 Some authors have suggested that this controversy may be related to the presence of many confounding variables, as well as the complexity of the auditory system. 34 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“… 37 , 38 Some authors have suggested that this controversy may be related to the presence of many confounding variables, as well as the complexity of the auditory system. 34 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other studies that investigated the effects of diabetes on hearing function did not remove confounding factors such as exposure to noise 22,26,27, gender 22,26,28, age 26, and hypertension 6,9,16.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the cases (4 of 6) of hearing loss following methadone abuse have been reportedly shown fully and speedy recovery and only two case reports showed persistent SNHL (4, 8). The findings of these case reports suggested that the reversible or irreversible methadone induced SNHL depends on the duration and time of exposure as well as the health status of drug users (10). Christenson and Marjal (18) reported two patients of sudden SNHL after methadone abuse, though the hearing loss in both cases reversed completely within 24 h. However, none of our patients had history of taking an overdose of prescribed methadone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to conventional PTA, extra high frequency (EHF) audiometry technique identifies hearing thresholds within the range of 9,000–18,000 Hz (9). The EHF assessment has been used for early detection of hearing loss attributable to lesions located in the base of the cochlear duct and may indicate alterations even before the characteristic effects appear in the conventional frequency range like noise induced hearing loss and ototoxicity (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation